A qualidade da informação contábil e o risco sistemático nos países emergentes - Gomes, Victorya Maria dos Santos (2023)
Based on a framework on the relationship between the quality of accounting information and systematic risk, the purpose of this study is to analyze how the interaction between the country's information environment and the quality of accounting information is associated with the sensitivity of companies to systematic risk in emerging countries. The data was collected from non-financial companies in the Thomson Reuters Eikon database. The sample consisted of information from 11,586 companies for the period from 2000 to 2021, totaling 202,193 observations for the entire period. The data was analyzed using multivariate panel data regressions. To determine the panel model to be used (fixed, random or POLS effects), tests such as Breusch-Pagan, Chow and Hausman indicated that the panel data model with random effects was the most appropriate. So, first we tried to measure systematic risk using the Beta coefficient and the quality of accounting information using two metrics: Dechow and Dichev (2002) and Modified Jones (1991). Subsequently, an attempt was made to identify the country information environment - CIE, formed by means of an index, using the Principal Component Analysis - PCA technique. The results obtained suggest that the quality of accounting information has an explanatory relationship with the sensitivity of companies to systematic risk in emerging markets. In addition, the study also found evidence that variables that control the level of the company, such as indebtedness and the Herfindal index, play an important role in these markets when associated with exposure to systematic risk. When analyzing the interaction between the country's information environment and the quality of accounting information in relation to sensitivity to systematic risk, we observed evidence of a negative and significant relationship when evaluating the quality of information using the Dechow and Dichev (2002) model, as well as a positive and significant relationship when using the Modified Jones (1991) model. The main contribution of this study lies in demonstrating that the quality of accounting information is associated with the sensitivity of companies to systematic risk in emerging countries. We cannot say with certainty whether factors such as better global governance indicators, together with the quality of accounting information in these countries, generate expectations in the market that may increase or decrease exposure to systematic risk.